Situational Leadership Style, Work Environment And Work Commitment To Improve The Performance Of Lecturers Of Higher Ed-ucation Foundation Rumpun Lelemuku - Bwarlely, Yonas; Latupapua, Conchita Valentina; Lewaherilla, Novalien Carolina (SEAN Institute, 2024)
The type of research used in this research is quantitative research. The data used in this study are secondary data and primary data. Data collection techniques used in this study were observation, interviews, documentation and questionnaires. The population used in this study was 40 lecturers at Lelemuku Saumlaki University. The sample used in this study was 40 respondents, as a sampling method was used, namely total sampling, in which the total population was used as a sample. Therefore the number of samples used in this study were 40 lecturers at Lelemuku Saumlaki University. The data analysis technique used is multiple linear regression analysis assisted by using SPSS 26 software.Situational leadership style, work environment and organizational commitment partially and simultaneously significant effect onperformance of Lelemuku Saumlaki Higher Education Foundation lecturers.